Century of the Angklung Journey and Its Establishment in Thailand - Poonpit Amatyakul (IJCAS (International Journal of Creative and Arts Studies), 2019)
Both Thai and Javanese have been with lifelong cultural friendship for over 250 years. Thai people enjoyed the Panji storytelling since the late 1700’s andhave been using Panji as written Thai poetic literature and for court theatre over2 centuries. We shared the same brass knobbed gong culture with its pentatonic(Slendro) and septatonic (Pelog) equidistance scales. The angklung, bambooshaking instrument, were brought as a gift to royal children by HM King Rama the V to Siam since 1871 but the ensemble were not set up until our great court musician named Jangwang Sorn Silapa-banleng, took the instruments from Sunda West Java to Bangkok in 1908, later, he established the very first ThaiAngklung Ensemble played several songs he composed in pentatonic scalesame way he heard in the Javanese Islands. Since then, the bamboo angklungwere made with the Thai native bamboo followed by the nationwide uses. Thispaper describes the Angklung Journey from West Java to Thailand showing thehistoric photographs of Thai Angklung music teachers, their houses ofAngklungs and the music they composed. Today, Thai Angklung were used forchildren classroom music. DVD and Musical Disc of Thai Angklung will bedemonstrated, bringing both music knowledge and enjoyment to show thecross cultural examples of the two nations.